The Silver Lining of a Pandemic Disruption in Academia - Vicky Johnson (Academic Chairpersons Conference Proceedings, 2022)
The pandemic caused by COVID-19 has undoubtedly been a disruptive force and has caused many challenges in academia. However, disruptions can also bring innovation and progress. This presentation will gather and summarize some of the positive consequences of the pandemic disruption from the department head perspective.
Keywords: pandemic disruption innovation technology arts